How do monetary and fiscal determinants affect inflation? Evidence from Azerbaijan - Gulaliyev, Mayis; Maharramov, Eldaniz; Alekperov, Ashraf; Hamidova, Lala; Novruzova, Zemfira (Asian Economic and Financial Review, 2025)
By employing OLS, Robust OLS, and ARDL models, the research evaluates the effects of minimum wages (both in PPP and national currency), government expenditures, and unemployment on inflation. The results demonstrate that government expenditures significantly and positively influence inflation in both short- and long-term perspectives. Minimum wages in the national currency are shown to increase inflation in the short run but exhibit a reducing effect with a time lag. Conversely, minimum wages measured in PPP have a deflationary effect, reflecting their stabilizing influence on purchasing power and consumer prices. Unemployment is found to reduce inflation in the short term, aligning with the Phillips Curve theory, while past unemployment levels display a delayed positive effect on inflation, underscoring the complex nature of the relationship. The study highlights the crucial role of fiscal policy in managing inflation in Azerbaijan, particularly in a resource-dependent economy. Furthermore, the impact of Azerbaijan’s 2015 currency devaluation was analyzed using a dummy variable approach, confirming no significant structural break in the inflation determinants post-devaluation. These findings provide valuable insights for policymakers in implementing effective inflation control strategies through employment policies, wage regulation, and government spending adjustments.